Microsoft SharePoint 2007 technologies : planning, design and implementation - Laahs, Kevin (Digital, 2008)
SharePoint provides a vital service to businesses--content sharing over Intranet and Internet sites. Microsoft is investing tons of research and development money into content sharing technologies: SharePoint is the ""next big thing"" for MS Office users, especially in a world where many work teams are becoming geographically dispersed. SharePoint 2007 is a big improvement over former releases, due to enhanced security, better search capabilities, and more robust functionality. Lots of change means that users will have to come up to speed on the new enhancements. With SharePoint 2007